Why software testing is sometimes ineffective: two applied studies of positive test strategy. - Teasley, Barbee E.; Leventhal, Laura Marie; Mynatt, Clifford R. (Journal of Applied Psychology, 1994)
The term positive test strategy describes the tendency to test a hypothesis with test cases that confirm (i.e., aim to support) rather than disconfirm the hypothesis. Most demonstrations of this phenomenon have involved relatively abstract problems. The authors suggest that people use a positive test strategy in a more applied setting as well, that is, in computer software testing. In 2 experiments, they examined how Ss with varying expertise performed functional testing of software. There was substantial evidence of the use of a positive test strategy: Ss tended to test only those functions and aspects of the software that were specifically described in the specifications as what the software was supposed to do. This effect was only partially mitigated by increasing expertise among testers and by more complete program specifications. Reprinted by permission of the publisher.